The Consumption of Tuak Increases Risk of Central Obesity among Adult Males at Karangasem, Bali - I Ketut Sudiana; I Wayan Gede Artawan Eka Putra; Pande Putu Januraga (Universitas Udayana, 2016)
Background and purpose: Traditional alcohol beverage known as risk factor of central obesity. The prevalence of central obesity in adult males in Karangasem is high and 40% of the population have drink habits of traditional palm wine (locally called tuak) with high sucrose and glucose. This study aims to determine the relationship between the consumption of tuak with the prevalence of central obesity among adult males. Methods: The study is cross-sectional with samples consisted of 220 men aged 18-65 years selected by probability proportional to size. The data were collected by the researcher using structured interview and direct measurement. Data were analyzed using STATA 12.1 by univariate, bivariate (chi-square test) and multivariate using logistic regression. Results: The study found that the prevalence of central obesity among adult males in Karangasem was 8.18% and respondents who consumed tuak was 53.18%, consumed alkohol of non tuak was 4.09% and 42.73% did not consume any alcohol. Multivariate analysis showed that variables associated with the prevalence of central obesity were heavy drinker of tuak (AOR=6.55; 95%CI: 1.45- 29.65), the quantity of tuak consumption (AOR=1.14; 95%CI: 1.03- 1.25), duration of tuak consumption (AOR=1.12; 95%CI: 1.04-1.20), consumption of other local wine (called arak) (AOR=3.86; 95%CI: 1.36-10.95. Education was found to reduce risk of obesity (AOR=0.32; 95%CI: 0.11-0.96). Conclusion: The consumption of tuak increases risk of central obesity among adult males in Karangasem Bali.